Pengembangan Healthy Nata De’melon Untuk Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi - Marni Febrianti; Yektiningtyastuti Yektiningtyastuti (Universitas Malahayati, 2025)
ABSTRACT Hypertension is defined as having a systolic blood pressure of 140 mmHg or higer and a diastolic pressure of 90 mmHg or higher. Treatment of hypertension includes both pharmacological and non-pharmagocological approaches. The recommended non-pharmacological treatment is to increase the consumption of foods containing diuretics (potassium). Melon fruit is known as a fresh fruit that contains a lot of water and is high in potassium. Develop nata from melons (Healthy Nata De'Melon) to lower high blood pressure. This study used the Research and Development method. The product trial was carried out by giving Healthy Nata De'Melon 250 ml to hypertensive elderly who were not taking antihypertensive drugs 2 times a day (morning and evening) for 7 days. After identifying the problem and collecting data, researchers developed the Healthy Nata De'Melon product. Validation of Healthy Nata De'Melon products is carried out through expert tests (3 nutritionists), and laboratory tests. The results of product validation from expert tests by hospital and health center nutritionists obtained a score of 39 (feasible), and from culinary experts a score of 34 (feasible). The results of laboratory tests obtained potassium content = 1,669 ppm (mg/L). The results of the product trial on 6 elderly respondents obtained the average systolic blood pressure before consuming Healthy Nata De'Melon = 158.3 mmHg, after the trial = 137.5 mmHg. Average diastolic blood pressure before consuming Healthy Nata De'Melon = 90.1 mmHg, after the trial = 80.6 mmHg. There was an average decrease in systolic blood pressure of 20.8 mmHg and a decrease in diastolic blood pressure of 9.5 mmHg after consuming Healthy Nata De'Melon. Healthy Nata De'Melon can used to decrease blood pressure in the elderly with hypertension. Keywords: Blood Pressure, Elderly, Healthy Nata De’Melon, Hypertension ABSTRAK Hipertensi adalah keadaan denyut nadi siastolik 140 mmHg atau lebih dan diastolik mencapai 90 mmHg atau lebih. Pengobatan hipertensi dibagi menjadi dua, yaitu farmakologi dan non farmakologi. Pengobatan non farmakologi dapat dilakukan dengan memperbanyak konsumsi makanan yang mengandung zat diuretika (potassium). Buah melon dikenal sebagai buah segar yang mengandung banyak air dan tinggi potassium. Mengembangkan nata dari buah melon (Healthy Nata De’Melon) untuk menurunkan tekanan darah tinggi. Penelitian ini menggunakan metode Research and Development. Uji coba produk dilakukan dengan memberikan Healthy Nata De’Melon 250 ml pada lansia hipertensi yang sedang tidak mengonsumsi obat antihipertensi 2 kali sehari (pagi dan sore) selama 7 hari. Setelah mengidentifikasi masalah dan mengumpulkan data, peneliti mengembangkan produk Healthy Nata De’Melon. Validasi produk Healthy Nata De’Melon dilakukan melalui uji expert (3 orang ahli gizi), dan uji laboratorium. Hasil validasi produk dari uji expert oleh ahli gizi rumah sakit dan puskesmas diperoleh skor 39 (layak), dan dari ahli tata boga diperoleh skor 34 (layak). Hasil uji laboratorium diperoleh kandungan potassium = 1.669 ppm (mg/L). Hasil uji coba produk pada 6 responden lansia diperoleh rata-rata tekanan darah sistolik sebelum mengonsumsi Healthy Nata De’Melon (pre-test) = 158,3 mmHg, setelah uji coba (post-test) = 137,5 mmHg. Rata-rata tekanan darah diastolik sebelum mengonsumsi Healthy Nata De’Melon (pre-test) = 90,1 mmHg, setelah uji coba (post-test) = 80,6 mmHg. Terdapat penurunan rata-rata tekanan darah sistolik 20,8 mmHg dan penurunan tekanan darah diastolik 9,5 mmHg setelah mengonsumsi Healthy Nata De’Melon. Healthy Nata De’Melon dapat digunakan untuk menurunkan tekanan darah pada lansia dengan hipertensi. Kata Kunci: Healthy Nata De’Melon, Hipertensi, Lansia, Tekanan Darah